Role of immunotherapy in ovarian cancer: a narrative review - Romanchik, D; Albukhari, A; Artibani, M; Ahmed, AA (AME Publishing Company, 2022)
Background and Objective: Ovarian cancer (OC) is a deadly gynaecological cancer with limited successful treatment options; approximately 70–80% of patients relapse, even those who initially respond well to treatment. It has been recently suggested that relapse occurs due to dormancy, an inactive cellular state which can evade traditional therapeutics targeting highly proliferating cells through different mechanisms. One is immune evasion, which conceals tumour cells from the body’s natural defence system. The cells can modulate their immunogenicity and that of the host to overcome the opposing tumour-immune system operation. Therefore, developing immunotherapies, which function to arm the host immune system against the tumour, is vital to patient survival. Considering the successes of immunotherapies in other cancers, this review will outline various tumour immune evasion strategies within its complex microenvironment and examine current significant developments in immunotherapies to inflame the ovarian tumour and overcome the resistance such that no cell is left behind. Methods: A PubMed search prioritising all types of literature since 2010 was conducted using the keywords “ovarian cancer”, “epithelial ovarian cancer”, “immunotherapy”, “immune evasion”, and “relapse” in various combinations. Secondary searches and other citations were based off reference lists. Key Content and Findings: Numerous molecular and cellular modifications are utilised by OC cells to evade the immune system. Further, the tumour microenvironment creates a physical barrier to immune infiltration and an immunosuppressive environment. In response, many immunotherapies have been created to combat OC, including antibodies, vaccines, adoptive cell therapy (ACT), immunomodulators and immunogenic cell death (ICD) inducers. Conclusions: Most immunotherapies targeting OC are still in early stages and far from being used clinically. While combination therapy is suggested, it may also be beneficial to recruit various types of immune cells to the tumour. Awareness of immune evasion strategies is critical to treatment development and targeting relapse.